Luminescent Properties of Al2O3:xEu obtained by Rapid Combustion Synthesis. Issue 1 (May 2020) - Viesca-Villanueva, E.; Chavez, D.; García, C. R.; Esquivel, B.; Martínez-Sánchez, E.; Lopez-Badillo, C.M.
Abstract: In this work, Al 2 O 3 : xEu 3+ were synthesized by the combustion method. The atomic concentration percentage of En doping was varied (x = 0%, 1%, 3%, 5% and 7at%). Structural and morphological properties were analyzed by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) techniques, respectively. The XRD patterns of the pure (x = 0%) and Eu-doped (x=1at%) show the single Al2 O3 corundum phase. For the highest Eu-doped concentrations of x = 3%, x = 5% and x = 7at%, the Al2 O3 :xEu samples, present a mixture of phases of corundum (Al2 O3 ) and EuAlO3 (perovskite). SEM images show irregular grains with average sizes in the range of 0.1 - 78.8 μm. Photoluminescence (PL) analysis show that all Eu-doped Al2 O3 samples exhibits intense red-emission. PL spectra show two main peaks at 615 nm ( 5 D0 ° 7 F2 ) and 700 nm ( 5 D0 ° 7 F4 ). The x = 3at% Eu-doped sample presents the highest intensity under 256 nm excitation. CIE coordinates were calculated from the PL spectra, values around x= 0.6 and y= 0.3 (red emission) were obtained from all samples. Due to its strong luminescence those Al2 O3 :xEu phosphors could be good candidates for components in solid state lighting.